REPRODUCTIVE PERFORMANCE OF INTRASPECIFIC HYBRIDS OF BLUE SWIMMING CRAB (Portunus pelagicus) - Andi Aliah Hidayani; Yushinta Fujaya; Dody Dharmawan Trijuno; Moh. Tauhid Umar; Nita Rukminasari; Alimuddin Alimuddin; Gunarto Gunarto (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2022)
High exploitation of the blue swimming crab (Portunus pelagicus) has significantly reduced its wild populations. The domestication process of this species has been started; however, its breeding program has not yet been successful. Therefore, this study aimed to examine the reproduction performance of intraspecific hybrids of blue swimming crab from Sorong (Papua) and Barru (South Sulawesi), Indonesia. P. pelagicus from Sorong has a bigger size, while the crab from Barru has a better reproduction performance, including fecundity and egg diameter. Hybridization was conducted between crabs from Sorong and Barru with different combinations of broodstock, namely: Barru female ><Barru male, (BF><BM); Barru female ><Sorong male (BF><SM); and Sorong female ><Barru male (SF><BM). The results showed no significant difference in the fecundity and egg diameter between the three hybridization trials. The number of successfully spawned broodstock from BF><BM, BF><SM, and SF><BM were 3, 3, and 2 broodstock, respectively. Meanwhile, the mean values of egg fecundity from BF><BM, BF><SM, and SF><BM were 117, 109, and 151 eggs/g BW, respectively. Furthermore, the mean values of broodstock fecundity per crab were 7,797 eggs, 10,103 eggs, and 10,605 eggs, while the mean values of egg diameter were 0.58 mm, 0.57 mm, and 0.62 mm, respectively. In conclusion, the intraspecific hybridization was successfully carried out between the Barru and Sorong crab populations showing no differences in the fecundity values and egg diameter between the three crosses. The successful spawning between female crabs from Sorong and male crabs from Barru was higher than that of female crabs from Barru and male crabs from Sorong.